2021
DOI: 10.1111/eje.12736
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 on dental education in Europe: The students' perspective

Abstract: Introduction: COVID-19 pandemic impacted dental students and postgraduate residents world-wide, forcing them to rapidly adapt to new forms of teaching and learning. Dental school leaderships needed to ensure the academic continuity, therefore the majority of the in-person actives were transitioned into a virtual setting. The aim of this study was to identify students' perception regarding the measures taken to adapt during the pandemic by different dental schools in the European Region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 14 publications
(25 reference statements)
4
20
0
Order By: Relevance
“…This ensured that they could stay in contact and not suffer from total isolation. These findings are also supported by a recent study made in different dental schools in the European region [ 47 ]. In addition to this, given the potential for psychological problems among students and academic staff induced by personal, social, emotional and academic situations [ 6 , 12 , 33 , 46 , 48 , 49 ], the Grigore T. Popa University of Medicine and Pharmacy Iasi offered guidance and emotional support on its online platform, via professional counseling sessions [ 33 , 50 , 51 ].…”
Section: Discussionsupporting
confidence: 88%
“…This ensured that they could stay in contact and not suffer from total isolation. These findings are also supported by a recent study made in different dental schools in the European region [ 47 ]. In addition to this, given the potential for psychological problems among students and academic staff induced by personal, social, emotional and academic situations [ 6 , 12 , 33 , 46 , 48 , 49 ], the Grigore T. Popa University of Medicine and Pharmacy Iasi offered guidance and emotional support on its online platform, via professional counseling sessions [ 33 , 50 , 51 ].…”
Section: Discussionsupporting
confidence: 88%
“…This was consistent with Agius et al [ 20 ], who showed that female dental students experienced more concerns about exam changes and loss of manual skills than the male students during the pandemic. Other studies point out the loss of manual skills as the most prominent stressor among dental students [ 20 , 34 ]. Furthermore, exam-related stress is also among the biggest stressors under normal circumstances [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the described platforms in many cases cannot replace full-time teaching, especially when it comes to teaching medicine, dentistry, etc. Vaccination partially helped to restart full-time learning, but a virtual environment was also used [4][5][6][7][8][9][10]. In addition, a study [7] focusing on the online dental education form stated that up to 50% of respondents (n = 435) spent less time in education and 30% (n = 265) of them spent more time.…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination partially helped to restart full-time learning, but a virtual environment was also used [4][5][6][7][8][9][10]. In addition, a study [7] focusing on the online dental education form stated that up to 50% of respondents (n = 435) spent less time in education and 30% (n = 265) of them spent more time. Satisfaction with teaching also brought differences of opinion regarding remote learning, where 44% (n = 382) of respondents were satisfied and 31% (n = 279) of respondents were not satisfied with the current learning form.…”
Section: Introductionmentioning
confidence: 99%